2011
DOI: 10.1097/mco.0b013e3283479109
|View full text |Cite
|
Sign up to set email alerts
|

Sleep and obesity

Abstract: Purpose of review This review summarizes the most recent evidence linking decreased sleep duration and poor sleep quality to obesity, focusing upon studies in adults. Recent findings Published and unpublished health examination surveys and epidemiological studies suggest that the worldwide prevalence of obesity has doubled since 1980. In 2008, 1 in 10 adults was obese, with women more likely to be obese than men. This obesity epidemic has been paralleled by a trend of reduced sleep duration. Poor sleep quali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
255
4
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 433 publications
(271 citation statements)
references
References 80 publications
(101 reference statements)
7
255
4
5
Order By: Relevance
“…However, there appears no consistency in whether the period of sleep loss (either in hours lost per night, or 5 duration of intervention) is related directed to the plasma leptin levels reported. Interestingly in the present study, reduction of leptin was observed only in the third week of sleep reduction and coincided with an increase in bodyweight, which initially appears counterintuitive but corresponds well to what is found in cohort studies (reviewed by [40]). Leptin expression may be inhibited directly by catecholamines [41] .…”
Section: Resultssupporting
confidence: 54%
“…However, there appears no consistency in whether the period of sleep loss (either in hours lost per night, or 5 duration of intervention) is related directed to the plasma leptin levels reported. Interestingly in the present study, reduction of leptin was observed only in the third week of sleep reduction and coincided with an increase in bodyweight, which initially appears counterintuitive but corresponds well to what is found in cohort studies (reviewed by [40]). Leptin expression may be inhibited directly by catecholamines [41] .…”
Section: Resultssupporting
confidence: 54%
“…The clarification of the relative contribution of endogenous and exogenous input to the diurnal rhythm of a physiological system is of particular relevance for understanding the influence of our modern 24/7 lifestyle on the well-being of individuals. Owing to social constraints many rhythmic behaviors such as sleep/wake and food intake/fasting cycles often no longer align with their endogenous pattern controlled by the circadian clock (Scheer et al 2009, Beccuti & Pannain 2011. Shift workers are an obvious example.…”
Section: Endocrine Rhythms: Clock Vs Behavioral Regulationmentioning
confidence: 99%
“…In our experience this is provoked by physical impairment such as Sleep Apnea and mental factors related to neuroendocrine facets and anxiety structure. Moreover, insomnia contributes to obesity provoking psychosocial impairment and a reduction of physical activity [66][67][68][69]. In our sample, IND is predominantly associated with maladaptive eating behaviors particularly grazing and sweet-eating.…”
Section: Insomnia Disorder: Indmentioning
confidence: 86%